Tribological behaviors of Ta-10W alloy at elevated temperature - Xia, Haiqing; Xu, Yi; Duan, Jing; Li, Shaoxuan; Jiang, Nan; Zhu, Shuai; Lei, Yaping; Shi, Pengfei; Tang, Jiancheng (Frontiers in Materials, 2023)
The purpose of this study was to experimentally research the tribological behaviors of Ta-10W at elevated temperatures and the effects of temperatures on the friction coefficient and the wear rate of Ta-10W in sliding wear. It was found that the main wear mechanism of the material at 100 ℃ was abrasive wear, as well as adhesive wear and slight oxidative wear occurred at 200 ℃ and 300 ℃. The friction coefficients increased as the temperature rose, which was attributed to the increase in metal viscosity at elevated temperatures. The wear rate gradually decreased with the temperature rising, such that there was a conversion from severe wear to light wear. At 200 ℃ and 300 ℃, a large amount of stable oxide film covered the scar surface, resulting in decreased wear rate.